Tensions in Communication at Workplace: A Systematic Literature Review - Nguyen, Cuong; Duc, Nguyen Minh (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2025)
Communication is essential for organizational effectiveness but often becomes a source of tension—among colleagues, between employees and managers, and in employee–customer interactions. When left unmanaged, these tensions can hinder collaboration, reduce employee well-being, and impair service performance. This study presents a Systematic Literature Review (SLR) of empirical and theoretical research from 1989 to 2021, aiming to provide an integrated understanding of communication tensions in organizational contexts. Drawing on key frameworks such as Emotional Contagion Theory, Organizational Paradox Theory, Uncertainty Reduction Theory, and Empathy Theory, the review identifies three primary sources of communication tension: employee–employee interactions, employee–manager relationships, and employee–customer engagements. A key finding is the role of mindset—particularly paradoxical thinking—as a cognitive-emotional mechanism that helps reframe tensions into opportunities for adaptive action. Using the PRISMA method for transparency and rigor, the review highlights common drivers of tension such as role ambiguity, power hierarchies, emotional labor, and conflicting expectations. Instead of viewing tensions solely as dysfunctional, the review emphasizes their potential to foster organizational learning, creativity, and innovation—when approached constructively with emotional intelligence and empathy. The study also notes theoretical fragmentation and calls for more integrative, multi-level research models. It identifies underexplored areas including team-level dynamics, cross-cultural differences, and frontline service roles. To address these gaps, the review proposes seven conceptual propositions and introduces an integrative framework for future research and practical application